“Gestión de créditos y la recuperación de la cartera para mejorar la rentabilidad en la Cooperativa de ahorro y crédito Futuro Lamanense 2020 provincia cotopaxi cantón La Maná” - Cedeño Garcia, Karen Kaina (2021)
The research work was developed in the Cooperativa de Ahorro y Crédito Futuro Lamanense of the canton La Maná, which was proposed with the objective of analyzing credit management and portfolio recovery to improve profitability in this financial institution. For which a descriptive research methodology of bibliographic and explanatory type was used, which served for the search of information with which the theoretical framework was structured; The interview and survey techniques were also applied, as well as the structured questions questionnaire instrument was used, as results it was obtained that in the study of the procedures used in the granting of credit and its portfolio the Cooperative does not check and verify the socioeconomic situation of the applicants, lack of monitoring or verification of the economic situation of customers, simplicity in the documentary requirements, among others; with the financial analysis through indicators it was obtained that in 2020 a profitability on sales of services rendered of 0. 13% unlike the year 2019 that a profitability of 0.16% was obtained, the income for the year 2020 had a participation of 0.13% higher than 2019; with the proposed manual of procedures and policies of credit and portfolio management it is intended to help improve the financial situation of the Cooperative.